Microssistemas eletroforéticos e dispositivos à base de papel: avanços instrumentais, incorporação de nanomateriais e diagnósticos clínicos - Gabriel, Ellen Flávia Moreira (2016)
This work describes several instrumental improvements to electrophoretic microchips (MSE) and microfluidic paper-based analytical devices (μPADs). The improvements are showed in terms of fabrication process, modification steps, control of sample volume and detection system. First off, a CO2 laser engraver was proposed to produce microchannels on a polymethyl methacrylate (PMMA) surface. All parameters were previously optimized in order to obtain a channel with the smallest dimension. Channels with 80 μm of deep and width were fabricated. MSE was coupled with amperometric detection and this work showed for the use of a decoupler produced by a mixture between PDMS and sugar the first time. The proof-of-concept testing of the final device demonstrated the analysis of a model mixture of phenolic compounds within 200 s with baseline resolution. Injection and control of the solution inside the microchannel was the another parameter improved during the development of this project. Hydrodynamic injector was developed using an electronic micropipette. The dispenser function of the micropipette can be explored to inject fractioned sample volumes inside the microchannel. The volume equaling 0.6 μL was considered ideal to completely fill the injection channel. In order to have better control of the sample volume, microdevices with different configuration were proposed. A microdevice with two auxiliary channels (split configuration) was select to realize the experimental part. When compared to electrokinetic injection, hydrodynamic showed better analytical performance including correcting the bias effect, which is the main problem related to electrokinetic injection. μPAD surface was modified by two different methodologies, using silica nanoparticles and chitosan. The modification process was used to solve the drawback related to the non-homogeneity or uniformity of color development in the detection zone. Silica nanoparticles and chitosan were incorporated on the cellulose surface to function as a new support to immobilize the selected enzyme. The modification process with both the nano and bio compounds improved the analytical performance, increased the reliability of the low cost platform and decreased the limit of detection (LD) of colorimetric system. The resulting LD for the glucose and uric acid assays were 23 and 37 μM, respectively. The enhanced analytical performance of modified the μPADs ensured for the first time the colorimetric detection of glucose in tear samples from four non-diabetic patients. The found concentration levels ranged from 130 to 380 μM.